Elucidating Template-To-Precursor Interactions for Synthesizing Highly Active Single Atomic Fe―N―C Electrocatalysts for the Oxygen Reduction Reaction - Kim, Dong-Gun; Park, Subin; Choi, Yuna; Lee, Eun-Hee; Cho, Yoonbin; Jung, Jae Young; Kim, Nam Dong; Kim, Pil; Yoo, Sung Jong (John Wiley & Sons Inc., 2024)
Iron- and nitrogen-doped carbon (Fe & horbar;N & horbar;C) catalysts have garnered attention owing to their high oxygen reduction reaction (ORR) activity, which is comparable to that of Pt/C catalysts. Among the various methods for designing Fe & horbar;N & horbar;C catalysts, the use of templates has been emphasized as a means to create hierarchical porous structures. This strategy has enabled the achievement of high ORR activity. In this study, we propose a method for manufacturing a catalyst with high ORR activity by maximizing the interactions between commercial silica templates and catalyst precursors. By manipulating the charge on the commercial silica surface and adjusting the pH of the dispersion, the catalyst fabricated through these methods exhibited superior ORR activity compared to Pt/C and recently reported nonprecious metal catalysts. Through diverse physicochemical and electrochemical analyses, we confirmed that this activity stems from the effectively generated hierarchical porous structure and the resulting high density of Fe & horbar;N active sites. This catalyst exhibited a kinetic current density of over 2.73 mA cm-2, which is more than double that of platinum and displayed a high ORR mass activity of 4.49 mA mg-1. This strategy holds significant potential for application in various carbon-based materials, paving the way for the development of highly efficient electrochemical energy devices.